Moving Forward : Building Research Capacity Related to Quebec's English-speaking Seniors - Quebec Community Groups Network (QCGN) (Quebec Community Groups Network (QCGN), 2014)
We are grateful to the Government of Quebec who funded the project through the Soutien aux initiatives visant le respect des aînés (SIRA) program. We’d like to acknowledge the project Steering Committee who demonstrated ongoing dedication and commitment to the project. Members are: David Cassidy, president of Seniors Action Quebec and committee co-chair; Sylvia Martin-Laforge, director general at QCGN and committee co-Chair; Cheryl Henry-Leggo, Vision Gaspé-Percé Now; Kevin Erskine-Henry, chair, South Shore Community Partners Network; Premela Pearson, secretary, Indian Women’s Circle; Jim Colmer, residepnt, James Colmer Consultation Inc; Jan Anderson-Toupin, Jeffery Hale; Al Abdon, Filipino Association of Montreal and Suburbs. The QCGN contracted Dr. Joanne Pocock as the lead researcher on this project. The project has deeply benefited from her guidance, professionalism and intellectual rigour.
Keywords: Official Language Minority Community (OLMC)

QCGN Community Leadership Awards - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN/Community Pleased with Funding from Secretariat - Quebec Community Groups Network (QCGN) (2018)

Allocution d’ouverture du QCGN devant la Commission de la culture et de l’éducation: Consultation générale et auditions publiques sur le projet de loi no 14 : Loi modifiant la Charte de la langue française, la Charte des droits et libertés de la personne et d’autres dispositions législatives - Quebec Community Groups Network (QCGN) (2013)

Moving Forward : Building Research Capacity Related to Quebec’s English-speaking Seniors : Executive Summary - Quebec Community Groups Network (QCGN)
While Quebec’s English-speaking seniors share many of the same needs and priorities as their French-speaking counterparts, as an official linguistic minority community (OLMC) they also have needs and priorities that are unique within the broader senior population. While there has been a great deal of research on Quebec’s demographic shift and its senior population, little - if - any attention has been paid to the specific needs and priorities of Quebec’s English-speaking seniors who are an official language minority community in Canada. One notable exception is the recent 2013 report entitled ‘Enjoying your senior years in your own language’ for the Office of the Commissioner for Official Languages, which employed 2006 Canadian census figures.